Design and Fabrication of a Car Sports Rims. - Nsimbe Laban (Kabale University, 2023)
The essence of a car rim is to provide a firm base on which the tyre is fixed. Original car rims are normally made from structure steel since it has a high strength to weight ratio that is a high strength per unit mass as compared to aluminium and magnesium alloys. Car rims are however required to be as light as possible so as to achieve more performance advantages such as quick acceleration and stopping, increased fuel efficiency and less strain on suspension components. The density of steel is higher than that of aluminium alloys thus steel is heavier as compared to aluminium alloys. There is need to design a lighter rim but maintaining the same strength as that of the original steel rim. This therefore calls for the design and fabrication of a sports rim using an aluminium aJloy. This study aims at designing and prototyping a car sports rim by casting of an aluminium alloy. In this study, all the stresses that act on the car rim and other requirements that must be met by the car rim were determined using design equations and free body diagrams. The rim components capable of withstanding these stresses were sized and drafted using solid works 2020. Fine element analysis was done on the 3D model using ANSYS 2021 R2 so as to check if the maximum stress in the design was below the allowable stress. A pattern to be used in making the mould cavity was designed and fabricated using wood processing techniques and casting of the rim was done using foundry practices from an aluminium alloy. The casted rim was then submerged in a pool of water, no bubbles were observed hence the rim was found to be air tight. A permanent mould is however recommended for this study so as to give a better surface finish and better dimensional tolerance. Low pressure casting is recommended that is by filling the mould cavity from the bottom so as to prevent the risk of air bubbles entering into the mould cavity hence minimizing casting defects. The casted rim should undergo more heat treatment processes so as to improve its strength and more tests including the impact tests should be done on the casted rim so as to ensure that it will perform its intended function before putting it in service.